2022
DOI: 10.1136/postgradmedj-2020-139329
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of home blood pressure monitoring 6 months after the risk and assessment management programme: does health literacy matter?

Abstract: BackgroundLittle is known whether patients with lower health literacy could retain the practice and knowledge of home blood pressure monitoring (HBPM) after an educational programme.MethodsA cluster randomised controlled trial in five primary care clinics recruited participants with uncontrolled hypertension. Clinics were randomised either to a HBPM group education (Risk Assessment and Management Programme (RAMP-group), or individual counselling of self-management (RAMP-individual). Health literacy was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, Al-rousan et al ( 27 ) reported patients’ willingness to monitor HBP but had concerns about their ability to do so. While patient education by clinicians and nurses can improve HBP technique ( 25 , 28 ), the time needed to instruct patients on HBP measuring protocols may not be feasible or available in busy clinical settings ( 18 ). Remote patient education through videos and online platforms could help improve HBP practices and techniques while working within the existing time constraints ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Al-rousan et al ( 27 ) reported patients’ willingness to monitor HBP but had concerns about their ability to do so. While patient education by clinicians and nurses can improve HBP technique ( 25 , 28 ), the time needed to instruct patients on HBP measuring protocols may not be feasible or available in busy clinical settings ( 18 ). Remote patient education through videos and online platforms could help improve HBP practices and techniques while working within the existing time constraints ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“… 53 Addressing uncertainties about correct procedures, inaccuracy of the readings, and technical issues in operating home blood pressure monitoring may also reduce patient concerns. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Although home BP may also trigger stress, it can provide reassurance for patients, and is associated with better adherence to BP-lowering medication and increased hypertension control rates (123)(124)(125). However, health literacy is an important factor in the use of home BP (126), and self-reported BP values, as with other data such as blood sugar in individuals with diabetes, may be inaccurate because of manipulation or human error (127).…”
Section: Factors Related To Patientsmentioning
confidence: 99%